A three-dimensional environmental hydrodynamic model, Fantom-Refined: Validation and application for saltwater intrusion in a meso-macrotidal estuary. (September 2019) - Veerapaga, Nagendram; Azhikodan, Gubash; Shintani, Tetsuya; Iwamoto, Naoya; Yokoyama, Katsuhide
Abstract: Many three-dimensional hydrodynamic models were developed to investigate saltwater intrusion in estuaries. However, the horizontal grid discretization remains a challenge to achieve high accuracy as well as to reduce the cost in grid generation and computation. A three-dimensional hydrodynamic simulator, Fantom-Refined was developed to address this issue. A structured gridding technique which enables a flexible local mesh refinement was used for the horizontal gridding to analyze the multi-resolution phenomena from coastal bay to river upstream. The model is based on a collocated finite-volume method with second or higher-order spatial and temporal numerical schemes. The model was calibrated and validated using the data measured in a meso-macrotidal Chikugo River estuary, Japan. The simulated water level and vertical and longitudinal distribution of salinity were reasonably matched with the measured data. The salinity intrusion length (SIL) and salinity interface gradient (SIG) calculated from measured and simulated results were in good agreement with R 2 value of 0.99 and 0.98 respectively. Although there were limited studies that reproduced continuous change in mixing condition from well mixed to salt wedge via partially mixed type, the present study successfully verified the change with intensive observations. The effect of channel meanderings and width on horizontal salinity distribution in the estuary was explained using the model results. Furthermore, the effect of horizontal grid resolution on saltwater intrusion and mixing conditions was investigated with three different grid resolutions and three different bathymetry resolutions. The results showed that both of the horizontal grid and bathymetry resolutions have significant effect on the prediction of the salinity distribution as well as the surface level in the estuary. Highlights: Fantom-Refined is described for the saltwater intrusion problem in estuaries. A flexible local mesh refinement technique is used for horizontal gridding. Calibration and validation is done with measured data in Chikugo River estuary. The effect of bathymetry on horizontal salinity distribution is investigated. The effect of grid resolution on saltwater intrusion and mixing condition is analyzed.